Access policy and the digital divide in patient access to medical records. Issue 1 (March 2017) - Ancker, Jessica S.; Nosal, Sarah; Hauser, Diane; Way, Christopher; Calman, Neil
Abstract: Background: Patient access to medical records may help them manage their healthcare. After socioeconomic disparities were found in early adoption of a patient portal, a safety net medical organization implemented universal access policies, a mobile portal app, and a Spanish version. The objective of this study was to estimate the effect of the changes on socioeconomic disparities in use of the patient portal. Methods: Retrospective cohort study of 129, 738 adult patients visiting the Institute for Family Health between 2011 and 2014. Logistic regression was used to model the odds of receiving portal access and using the portal. Results: In 2011, members of socioeconomically disadvantaged groups were less likely to receive offers to use the portal and subsequently to use it. In 2014, black patients became just as likely as other racial groups to use the portal, but publicly insured and uninsured patients were still less likely to become users. Uptake of the mobile app was slow. Conclusions: Replacing an opt-in policy with a universal access policy was associated with a large reduction in socioeconomic disparities between those who did and did not access their medical records. However, a small digital divide remained evident in use of the technology, probably due to structural factors beyond the control of the healthcare system such as lack of computer access by less affluent patients. Highlights: Patient access to medical records may help them understand their health and manage their healthcare. An opt-in policy for medical record access was associated with large socioeconomic disparities between those who did and did not access their medical records. Replacing the opt-in policy with a universal access policy nearly eliminated these disparities over 4 years.